Perancangan Filter Frame Instagram Untuk Hari Tata Ruang Nasional 2023 PT. Urban Spasial Indonesia Menggunakan Software Spark AR - Clara Oktavia Firdaus; Alfian Candra Ayuswantana (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In commemorating National Spatial Planning Day 2023, PT Urban Spatial Indonesia has crafted an Instagram filter using Spark AR software. This filter serves as a creative and interactive media and functions as an educational tool. Using a qualitative case study method, this research is organized by defining the concept and design of the filter. The evaluation indicates a positive response with a significant number of user engagements. It is hoped that the design of this filter can contribute to enhancing public awareness and appreciation for the importance of spatial planning.